Emotional Well Being among College Students and their use of Social Media (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Concerns have been raised by certain individuals over the impact that excessive usage of social media is having on the mental health of college students. During the course of this study, we will investigate college students in Kerala with the objective of determining the impact that their usage of social media has on their own mental health. For the purpose of selecting a sample of 1,590 undergraduate students from 35 different institutions, the descriptive survey approach used a technique known as simple random sampling. The participants were asked to complete out questionnaires that queried about their emotional well-being as well as their behaviours regarding social media. A number of statistical techniques, including the arithmetic mean, the t-test, the standard deviation, the Pearson product moment correlation, regression analysis, and others, were used in the process of analysing the data. The findings indicated that high levels of social media usage were linked to negative emotional impacts, such as increased levels of stress, anxiety, and feelings of isolation. On the other hand, pleasant emotional states including improved social support and self-esteem were connected with moderate social media use. The significance of these findings lies in the fact that college students should be cautious of their usage of social media and should strive to strike a good balance between the impact that both platforms have on their mental health. According to the findings of the study, excessive use of social media might have adverse effects on mental health, despite the fact that it may improve feelings of connection. Since this is the case, there is a need for an intervention that would promote healthy digital behaviours.